Development of The Principle of Beneficial Ownership Identification of a Corporation and Their Implications for Tax Paying Obligation - Rizky Imanuel Tampubolon; Umi Khaerah Pati (Universitas Sebelas Maret, 2024)
Business has a significant role in the Indonesian economy, contributing through tax revenue and foreign exchange. Nevertheless, violations such as manipulation and tax evasion by some companies can adversely affect economic growth. One strategy for tax avoidance is through Beneficial Ownership, especially with the treaty shopping scheme, which can result in significant losses in national tax revenue. The focus of this research is on the implementation of the